2019
DOI: 10.1029/2019gl082710
|View full text |Cite
|
Sign up to set email alerts
|

Electron Vorticity Indicative of the Electron Diffusion Region of Magnetic Reconnection

Abstract: While vorticity defined as the curl of the velocity has been broadly used in fluid and plasma physics, this quantity has been underutilized in space physics due to low time resolution observations. We report Magnetospheric Multiscale (MMS) observations of enhanced electron vorticity in the vicinity of the electron diffusion region of magnetic reconnection. On 11 July 2017 MMS traversed the magnetotail current sheet, observing tailward‐to‐earthward outflow reversal, current‐carrying electron jets in the directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…A recent study by Hwang et al () reported increased electron vorticity close to an EDR observed in the magnetotail by MMS. The authors concluded that the vorticity is driven by the drift of meandering electrons in the trueM^ direction that changes fast with an increasing distance from the current sheet.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A recent study by Hwang et al () reported increased electron vorticity close to an EDR observed in the magnetotail by MMS. The authors concluded that the vorticity is driven by the drift of meandering electrons in the trueM^ direction that changes fast with an increasing distance from the current sheet.…”
Section: Discussionmentioning
confidence: 58%
“…These vortices may work as seeds for the secondary flux ropes as they grow in size and couple with the magnetic field (Fermo et al, 2012;Huang et al, 2015;Zhong et al, 2018). In this event MMS observes the electron vortex closest to the MN plane and the largest shear in the electron velocity inM direction as observed in the magnetotail by Hwang et al (2019), not along the separatrices (LN plane). In this event the electron shear flow inM direction between the current sheet and the magnetic structure (Δv e,M ≈ 840 km/s) fulfills the the instability condition for the electron Kelvin-Helmholtz instability: Δv e,M > v A,eM ∕2, where v A,eM is the electron Alfvén velocity inM direction (Fermo et al, 2012).…”
Section: 1029/2019ja027192mentioning
confidence: 90%
“…The V e,l, O‐L reversal (250 ± 150 km/s in Figure 4b; marked by the vertical blue line) and the reversal in B l O‐L (Figure 4a; marked by the vertical black line) are separated by ~0.9 s, suggesting the displacement of the stagnant point from the X‐line along the l direction (Hasegawa et al, 2019; Hwang et al, 2019). Around the V e,l, O‐L reversal, the out‐of‐plane V e,m, O‐L (Figure 4b) increases and the parallel heated electron flux is enhanced (red arrow in Figure 4c); J·E′ is negative (Figure 4e), which represents a transfer of energy from the plasma to the fields and has been reported at the outer edge of the EDR (Hwang et al, 2017) or in association with waves (Swisdak et al, 2018; Figure 3k).…”
Section: Reconnection Occurring In/around the Flux Ropementioning
confidence: 99%
“…To confirm this speculation, Figure 3b shows the four‐spacecraft averaged magnetic field ( B ml ) in black, a hyperbolic tangent function ( B hl ) fitting to the averaged magnetic field in cyan, and the sum of B hl and the magnetic field from the contribution of electron vortex ( B vl ) in magenta. The contribution of the electron vortex to the magnetic field is calculated following the approach of Hwang et al (2019). Ampere's law predicts that the electron vorticity can generate perturbations in magnetic field, B vl = − μ 0 n e e (▽ × V e ) l (Δ s mn ) 2 , where μ 0 is the vacuum magnetic permeability, n e is the electron density, e is the electric charge, and Δ s is the spatial scale of the electron vortex, which is estimated by V e /▽ V e .…”
Section: Observationsmentioning
confidence: 99%